Evaluation of Cytotoxicity, Release Behavior and Phytopathogens Control by Mancozeb-Loaded Guar Gum Nanoemulsions for Sustainable Agriculture - Ravinder Kumar; Manju Nehra; Dharmender Kumar; Baljeet Singh Saharan; Prince Chawla; Pardeep Kumar Sadh; Anju Manuja; Joginder Singh Duhan (MDPI AG, 2023)
Chemical fungicides are the backbone of modern agriculture, but an alternative formulation is necessary for sustainable crop production to address human health issues and soil/water environmental pollution. So, a green chemistry approach was used to form guar gum nanoemulsions (NEs) of 186.5-394.1 nm containing the chemical fungicide mancozeb and was characterized using various physio-chemical techniques. An 84.5% inhibition was shown by 1.5 mg/mL mancozeb-loaded NEs (GG-1.5) against A. alternata, comparable to commercial mancozeb (86.5 ± 0.7%). The highest mycelial inhibition was exhibited against S. lycopersici and S. sclerotiorum. In tomatoes and potatoes, NEs showed superior antifungal efficacy in pot conditions besides plant growth parameters (germination percentage, root/shoot ratio and dry biomass). About 98% of the commercial mancozeb was released in just two h, while only about 43% of mancozeb was released from nanoemulsions (0.5, 1.0 and 1.5) for the same time. The most significant results for cell viability were seen at 1.0 mg/mL concentration of treatment, where wide gaps in cell viability were observed for commercial mancozeb (21.67%) and NEs treatments (63.83-71.88%). Thus, this study may help to combat the soil and water pollution menace of harmful chemical pesticides besides protecting vegetable crops.